High Catalytic Synergism between the Components of the Rhenium Complex@Silver Hybrid Material in Alkene Epoxidations. Issue 7 (18th May 2014) - Indra, Arindam; Greiner, Mark; Gericke, Axel Knop; Schlögl, Robert; Avnir, David; Driess, Matthias
Abstract The immobilization of a water‐soluble rhenium complex in metallic silver matrices has resulted in a highly efficient catalyst for epoxidation, which has better epoxidation catalytic activity than the individual components. This unprecedented synergism could be obtained only by using the novel immobilization methodology, and not by using the standard adsorption process. The composite catalyst has been fully characterized (by using XRD, TEM, SEM, energy‐dispersive X‐ray spectroscopy, and atomic X‐ray mapping), and the synergism has originated as a result of the proximity of the two components. Photoemission spectroscopic studies confirm the presence of +6 and +7 oxidation states of rhenium in metallic silver in the active catalyst.